Living Data : Making Sense of Health Biosensing - Roberts, Celia, 1968-; Mort, Maggie; Mackenzie, Adrian, 1962- (Book collections on Project MUSE., 2019)
As individuals increasingly seek ways of accessing, understanding and sharing data about their own bodies, this book offers a critique of the popular claim that 'more information' equates to 'better health'. Through case studies which focus on significant life changes, the authors examine the potential challenges related to people's changing relationships with traditional health systems as access to, and control over data shifts.